Substantive Usage of Adjectives and Participles in the Old Bulgarian Translation of the Book of Exodus - Желязкова, Веселка (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] The purpose of the article is to separate and describe the the substantive usage of adjectives and participles utilized in the oldest Slavonic translation of the Book of Exodus in comparison with the Greek original and the so-called “Old Bulgarian Canon”. Denominations of persons and denominations of abstract and concrete concepts are successively considered. The presented material shows that on one hand the substantive usage of adjectives and participles depends very heavily on the Greek text. On the other hand, it is not unfamiliar to the Old Bulgarian. The substantive usage of adjectives and participles (including multi-word formations) takes an important part in the vocabulary of the Book of Exodus and has to be specially allocated in the dictionary of this book, as well as in the historical dictionary of the Bulgarian language.